(untitled) (World Bulletin of Social Sciences, 2021)
This article is dedicated to the analysis of the ghazal "Ey, quyosh yuzing ochgin…" by Muhammad Reza Agahi, a skilled translator, poet and statesman. The article describes the structure of the ghazal, its poetic art, rhyme and spiritual aspects on a scientific basis. Here are some of the ones I found to be interesting: There are also enough conclusions about the author’s work